Anaplastic Ganglioglioma of the Pineal Region – A Case Report - Costa, Marcos Devanir Silva da; Centeno, Ricardo Silva; Reghin Neto, Mateus; Doria Netto, Hugo Leonardo; Campos Filho, Jose Maria; Paz, Daniel de Araujo; Rodrigues, Thiago Pereira; Telles, Bruno Augusto; Lancellotti, Carmen Lucia Penteado; Cavalheiro, Sergio; Chaddad-Neto, Feres (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
Introduction Gangliogliomas are tumors commonly found in the temporal lobe and related to seizures; their appearance in the pineal region is rarely described. This report characterizes the first case of anaplastic ganglioglioma of the pineal region.Case Report The authors describe the case of a 32-year-old woman that developed progressive headache. An MRI investigation revealed a pineal tumor. The patient tested negative for biomarkers and underwent surgery through supracerebellar infratentorial approach and achieved gross total resection of the tumor in a challenging location.Pathological analysis revealed a biphasic neoplasm with the following two distinct phenotypes in separate fields: an immature neuronal component with several atypical mitoses and a mature astrocytic component with bipolar cells, microcysts, and eosinophilic bodies. The Ki67/MIB1 proliferation index was 20–30% in localized hotspots. Based on the pathological findings, the tumor was defined as an anaplastic ganglioglioma World Health Organization (WHO) grade III.Discussion/Conclusion Gangliogliomas are classified as glioneural neoplasms based on the histologic findings described as a mixture of neoplastic astrocytes and neurons. Moreover, these tumors represent 0.4–1.3% of tumors of the central nervous system. Authors describe de novo anaplastic ganglioglioma as 1% of the largest series. Gross total resection and adjuvant treatment may play important role in patients' prognostic. In this case, due to the malignant anaplastic component of her tumor, the patient received treatment with temozolamide and radiotherapy after gross total resection of the lesion.
Keywords: pineal gland; brain tumor; malignant ganglioglioma